IMPLEMENTASI PERMAINAN DOMINO UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN MINAT BELAJAR SISWA KELAS V PADA PELAJARAN IPS DI SDN KEMUNING KECAMATAN SAMBIT KABUPATEN PONOROGO - Dian Nur Antika Eky Hastuti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
In the learning at school teachers play an important role to create an environment learned that can stimulate students with a maximum development. This study use sthe design of Classroom Action Research is done in two cycles. Data collection techniques used were observation with the observation sheet instruments that equipped with assessment guide lines and photographs as documentation, while the techniques of data analysis performed quantitative descriptive. The results of this study showed an increase in the quality of social learning. Comparison cognitive skills of students at the pre-cycle only 38%, whereas at the end of first cycle have 68,75%, and at the end second cycle there were 93,75%. While comparison interest learn students at the pre-cycle is 32,25%, first cycle is 82% and at the end second cycle there were 93,75%.